Integrating local wisdoms for improving students’ mathematical literacy: The promising context in learning whole numbers - Leton, Samuel Igo; Lakapu, Meryani; Dosinaeng, Wilfridus Beda Nuba; Fitriani, Nelly (IKIP Siliwangi and I-MES, 2025)
The gap in the decline in PISA scores is likely due to an abstract and contextually irrelevant approach to teaching mathematics, which often fails to connect everyday experiences that utilize the potential of local wisdom to make learning more engaging and culturally relevant. This research aimed to develop mathematics learning materials that integrate local wisdom to improve students' mathematical literacy skills. The study employed the Research and Development (R&D) method with the ADDIE development model. The developed learning materials incorporated elements of Timor local culture, including traditional houses, handwoven fabrics, and traditional games, as contextual tools to enrich the learning experience. The quality of the developed product was evaluated for three aspects: validity, practicality, and effectiveness. The validation results showed an average score of 93.1%, which is included in the very valid category. Product implementation showed a significant increase in trial results, with all students meeting the minimum competency criteria after using the learning materials. The final score of students' responses after using this developed product is 96.93%, categorized as very practical. The average N-Gain score of 0.76 significantly increased students' mathematical literacy skills. Feedback from students highlighted that learning materials inspired by local wisdom made the learning process more engaging and relatable. Teachers appreciated the inclusion of cultural elements, noting that they facilitated a deeper connection between mathematical concepts and students' everyday experiences. The research underscores the transformative potential of a culture-based approach in mathematics education.